2017
DOI: 10.13040/ijpsr.0975-8232.8(4).1582-89
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: ABSTRACT:The present study was designed to evaluate the effect of Helix aspersa crude extract on colonic injury resulting from hyperhomocysteinemia induced by feeding rat's high methionine diet. Wistar albino rats (200-250g) were divided into four groups. Hyperhomocysteinemia (Hhcy) was induced by methionine treatment (1g/kg/day) for 15 days. M group received only Methionine, MH and MP received Methionine and Helix aspersa Crude Extract (8g/kg/day) or Prednisolone (4 mg/kg/day) respectively at the 8th day unti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…It has also been widely reported that HHcy induces acute and chronic inflammatory events via NF-κB regulation [ 12 ]. In a neuroblastoma cell line, an induced high level of Hcy was demonstrated to boost NF-kB levels, and this was inhibited by the introduction of antioxidants [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been widely reported that HHcy induces acute and chronic inflammatory events via NF-κB regulation [ 12 ]. In a neuroblastoma cell line, an induced high level of Hcy was demonstrated to boost NF-kB levels, and this was inhibited by the introduction of antioxidants [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…For histological analysis, tissues were subjected to hematoxylin and eosin staining and observed by competent pathologists using a Leica DM6 microscope (Leica Microsystems SpA, Milan, Italy), associated with Leica LAS X Navigator software (Leica Microsystems SpA, Milan, Italy). Histological injuries were scored as previously reported [ 12 , 32 , 33 ]. Paraffin-embedded skin tissues with a thickness of 5 μm were stained with Masson’s trichrome, according to the manufacturer’s protocol (Bio-Optica, Milan, Italy) [ 34 , 35 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation